Indonesian pre-service teachers’ readiness for inclusive education: A perspective from a State Islamic University - Fithriani, Rahmah; Wahyuni, Mira; Hardiansyah, Dadang (Universitas Jambi, Indonesia, 2026)
This study aims to evaluate the readiness of pre-service teachers at the Faculty of Tarbiyah and Teacher Training, State Islamic University of North Sumatra, for inclusive education. A mixed-methods approach utilizing an explanatory sequential design was employed to gain a thorough understanding of prospective teachers' knowledge, attitudes, self-efficacy, and concerns about inclusive education. The quantitative poll included 298 students across 10 academic disciplines, of whom 44 were voluntarily selected for the Focus Group Discussion (FGD) session. Quantitative data were collected using an expert-validated questionnaire and analyzed descriptively with SPSS 25.0, while qualitative data were evaluated thematically. The findings revealed that the prospective teachers had favorable attitudes and self-efficacy toward inclusive education; however, they needed to enhance their conceptual knowledge and receive institutional support to be adequately prepared for inclusive learning activities.